Hubungan Pola Asuh Orang Tua dengan Perkembangan Bahasa Anak Usia Prasekolah di Tk Nurul Wadda Caringin Bogor Tahun 2024 - Sherly Nurul Padilah; Inas Syabanasyah; Solehudin, Solehudin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Language is used to communicate and interact with others. If supported by stimulation from parents, children's language development will be optimal. Good parenting will also support children's language development. The purpose of this study was to determine the relationship between parenting patterns and language development of preschool children at Nurul Wadda Caringin Kindergarten, Bogor in 2024. This type of research uses quantitative methods with correlational analytic research type and cross sectional design, Chis-square analysis test. Sampling was done by total sampling, involving 60 respondents. This research was conducted at Nurul Wadda Caringin Kindergarten, Bogor. The results of this study found that most of the parenting patterns were authoritarian parenting patterns as many as 24 people (40.0%). Language development of preschool children is mostly deviant as many as 42 people (70.0%). The Chis-square test shows that the p value = 0.001, so there is a relationship between parenting patterns and the language development of preschool children. Parents are expected to have the necessary knowledge to raise their children well and apply parenting methods that are appropriate for the age of the child, still considering the rights and wishes of the child.